Investigating the Effect of Stress-Coping Abilities on Stress in Practicum Training - Geok Kim Ngui; Yoon Fah Lay (Springer Singapore, 2018)
Practicum is a highly stressful situation whereby trainee teachers are subjected to a high-quality standard, deals with numerous students’ behaviour, adapt with the school climate and so forth. In this study, stress-coping factors comprising self-efficacy, subjective well-being and emotional intelligence experienced by 137 trainee teachers in the Sabah Teacher Education Institutions (TEIs) are associated with practicum stress. Resiliency Scale for Young Adults (RSYA), Teachers’ Sense of Efficacy Scale, the Emotional Intelligence Traits, Satisfaction with Life Scale (SWLS) and Rating Pre-Service Teacher Events for Stress Scale were adapted and used in this study. Collected data were analysed using the PLS-SEM approach. The result showed that self-efficacy and subjective well-being were significant predictors of resilience and practicum stress. It is hoped that this study will provide more understanding about practicum stress and stress-coping abilities so that appropriate orientation, content and practice during practicum can be planned and implemented in an effort to prepare high-quality educators.